Faktor yang Berhubungan dengan Kejadian Gangguan Akibat Kekurangan Yodium di Kecamatan Koto Tangah, Padang: Iodine Deficiency Disorder (IDD) - Helfi Agustin; Hary Budiman; Yaumi Faiza (Jurnal Kesehatan Komunitas, 2015)
Universal Salt Iodization is a national program to decrease Iodine Deficiency Disorder (IDD). According to the Indonesian National Standard ( SNI ) salt must contents 30-80 ppm of KIO3 or equivalent with 15 ppm of iodine. Untill 2011 Padang city still endemic of IDD (Rizalia, 2011). Sub district Kuranji, Bungus Teluk Kabung and Koto Tangah is the worst condition of IDD endemic. This study aimed to examine factors related to IDD prevalence in KotoTangah District. Independent variable is Iodine content in salt and iodized salt management at the household. Iodine content in salt was measured by iodometric titration determination tes. While the salt in household management was traced by using a list of questions and observations. Design applied to this research was a Cross Sectional Study. The number of samples were 46. Sample were selected by multistage random sampling technique. The sample unit was the mothers who had a child at class IV , V and VI in the elementary school. Results of the research found that 98.1 % iodine content in salt (KIO3) was in less category, ranged from 9.63 to 20.33 ppm. This research also found that the majority (88.7%) had poor management of iodized salt. There was no relationship between iodine content of salt and Iodine salt management at the household level with IDD prevalence.